Início tardio da terapia anti-retroviral entre pacientes acompanhados em dois serviços públicos de referência para o HIV/Aids em Belo Horizonte - Jose Roberto Maggi Fernandes (2008)
Introduction: The development of combination antiretroviral therapy (ART) has improved the quality of life and survival of patients living with HIV/AIDS. Many authors have shown that patients initiating ART with a CD4+ lymphocyte-T count (CD4 count) lower than 200 cells/mm is 3 associated with higher mortality rates and faster development of AIDS. Various guidelin s have recommended initiating ART for every patient with CD4 count lower than 350 cells/mm3 or clinical symptoms of severe immunodepression. Although the well-defined recommendations for ART initiation and the free access to ART and the availability of specialized clinical care for HIV-infected patients in Brazil, ART has been initiated in an advanced clinical stage for a significant proportion of patients. Objective: To verify the prevalence of delayed ART initiation and associated factors among HIV-infected in Belo Horizonte (MG), Brazil, 2001-2003. Methods: Cross-sectional study with 310 patientsenrolled in two public health centers who were initiating ART according to the Brazilian Ministry of Health guidelines. Delayed ART initiation was evaluated using data extracted from medical chart and semi-structured interview applied just after the first antiretroviral prescription. We defined delayed ART as initiating treatment with CD4 count lower than 200 cells/mm3 or clinical symptoms of HIV-associated severe immunodepression at the time of first antiretroviral prescription (Clinical category C; CDC, 1992). The magnitude of the associations was estimated using odds ratio with confidence interval of 95%. Multivariateanalysis was conducted using logistic regression. Level of significance considered was 0.05. Results: Among the 310 participants, most of them were male (63.9%) and did not have health insurance (76.1%). Approximately 37% of them were unemployed. More than one quartile of the individuals initiated clinical follow-up in the health services 90 days after being diagnosed with HIV infection and 75.2% started ART less than 4 months after the first medical visit. Most of the interviewees (63.5%) reported being tested for HIV because of health professional advice. More than one half of participants have no record of HIV-viral load before initiating ART as recommended. The prevalence of delayed ART initiation vas 68.4%. Multivariate analysis indicated that unemployment, being tested for HIV because of health professional advice, to have less than two medical visits during six months prior to ART initiation and time between first medical visit in the service and ART initiation less than120 days were independently associated with delayed ART initiation. Conclusions: The prevalence of delayed ART initiation was remarkably high in our sample. The association between unemployment and delayed ART initiation can indicate difficulty of access to laboratory monitoring and regular clinical follow-up. Moreover, being tested for HIV because of health professional advice suggests low self-perception for acquiring HIV infection by these participants. Finally, the association of variables such as less than two medical visits during the six months prior to ART initiation and time between first medical visit in the service and ART initiation lower than 120 days with the event could reflect late initiation of care for HIV/aids. Our results suggest that every patient 13 to 64 years-old should be offered HIV testing as this action could increase the rate of early HIV infection diagnosis and, consequently, those patients who tested positive could benefit from follow-up and antiretroviral therapy at adequate time. More studies evaluating the cost-benefit of that actionare necessary. These strategies should be done together with an adequate sheltering of the patients at the health services and counseling regarding risk behavior changes.